Standardization of questionnaire methods (MMPI and 16 PF) for adolescent examination - Goštautas, A.; Berneris, V.; Jurevičiūtė, E. (Psichologija, 1983)
Statistical standards and criteria for the evaluation of the adolescent's personality by such personality assessment methods as MMPI and 16 PF are presented. MMPI statistical standards are established for pupils of the 8th form and 16 PF statistical norms - for pupils of the 8th, 10th, and 11th forms. The usage of the above-mentioned standards makes it possible to interpret more exactly the results of examination of the adolescent's personality.
Keywords: MMPI; 16 PF; norms; adolescent; personality; testing